Detection of Proteinuria in Pregnancy: Comparison of Qualitative Tests for Proteins and Dipsticks with Urinary Protein Creatinine Index - Indu Saxena; Sangeeta Kapoor; Ramesh C Gupta (Journal of Clinical and Diagnostic Research, 2013)
Background and Objectives: Excretion of urinary protein increases to 300 mg/d (from up to 150 mg/d) in normal pregnancy. Values above this may be due to disorders that can endanger the patient or her pregnancy. Quantitative analysis of 24-hour urine is considered the gold standard for ascertaining daily protein excretion. Routine laboratory tests performed on spot urine samples indicate protein concentration in the particular sample, and can lead to diagnostic error if urine output is less or more than 1L/d. The Protein Creatinine Index (PCI) shows good correlation with 24-hour protein estimation. However, PCI varies with sex and race. We have correlated the results of qualitative estimation procedures and the dipstick values with protein creatinine index. Material and Methods: We measured protein and creatinine in spot urine samples obtained from 57 pregnant and 80 non– pregnant healthy women of 18–36 years, and calculated PCI. We also tested the samples qualitatively for proteins by routine tests and dipsticks. Results: Normal range of PCI in non–pregnant women, determined by a non–parametric method was 30–150. PCI was increased significantly in pregnancy (maximum increase in the third trimester). Amongst the qualitative tests, heat coagulation test gave the lowest percentage of false positives and a slightly higher percentage of false negatives compared to Heller’s nitric acid and sulphosalicylic acid tests, and dipsticks. Interpretations and Conclusions: We conclude that heat coagulation test be used for initial screening, with PCI being performed on all samples testing positive to rule out false positives.